Contained Rupture in HeartMate II Outflow Graft Bend Relief Disconnection. (March 2016) - Chua, Kim Chai; Tan, Teing Ee; Lim, Chong Hee; Kerk, Ka Lee; Sivathasan, Cumaraswamy
Thoratec recalled their HeartMate II ventricular assist device in March 2012 after some problems related to disconnection of the bend relief. Abrasion on the pump outflow graft caused by a disconnected bend relief is rare. We report the case of a 49-year-old man in whom a disconnected bend relief caused a puncture in the outflow graft, resulting in a contained hematoma, requiring outflow graft replacement.